The art of painting in acrylic - Call, Alicia VanNoy (Irvine, CA Walter Foster, 2014)
"From beautiful landscapes and seascapes to lifelike animals and compelling still lifes, 'The Art of Painting in Acrylic' features a vast array of easy-to-follow, step-by-step painting lessons from talented professional artist. With inspiration, instruction, and expert tips and tricks on virtually every page, 'The Art of Painting in Acrylic' is your all-inclusive resource and guide to mastering this versatile medium. Dive in and get started on your acrylic painting journey, and discover just how easy painting in acrylic can be!"--Back cover.
Introduction -- Chapter 1 : Still lifes with Linda Yurgensen -- Chapter 2 : Landscapes & seascapes with Varvara Harmon & Darice Machel McGuire -- Chapter 3 : Animals with Toni Watts -- Chapter 4 : Figures & portraits with Michael Hallinan -- Chapter 5 : Pop-art animals with Alicia VanNoy Call -- About the artists -- Index.
Includes index.
Keywords: Acrylic painting -- Technique; Painting -- Technique; aAcrylic painting -- Technique; aPainting -- Technique